2016
DOI: 10.1097/gox.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Internal Mammary Artery Perforators as Recipient Vessels in Microvascular Breast Reconstruction—An Analysis of 515 Consecutive Cases

Abstract: Background:The usage of internal mammary artery perforators (IMAPs) has been described in autologous breast reconstruction although IMAPS are not yet considered standard recipient vessels. It remains unclear if these vessels can be safely used in large flaps after radiation therapy or in delayed breast reconstruction.Methods:Over a 2-year period, 515 free flaps for autologous breast reconstruction were performed on 419 patients by 2 surgeons (S1 and S2). In a retrospective analysis, time of reconstruction, isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
1
28
0
2
Order By: Relevance
“…It is worth mentioning that the IM artery perforators have been successfully used for breast reconstruction in several series (Follmar et al, 2011;Hamdi et al, 2004;Vollbach et al, 2016). The main goal of attempting this approach is lowering surgical morbidity.…”
Section: Lorenzetti Et Al Investigated the Effects Of These Parametementioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the IM artery perforators have been successfully used for breast reconstruction in several series (Follmar et al, 2011;Hamdi et al, 2004;Vollbach et al, 2016). The main goal of attempting this approach is lowering surgical morbidity.…”
Section: Lorenzetti Et Al Investigated the Effects Of These Parametementioning
confidence: 99%
“…The reported advantages appear to be sparing the IM vessels for cardiac surgeons and avoiding thoracic and abdominal morbidity (Hamdi et al, 2004;Vollbach et al, 2016). It was also hypothesized that this approach might lower operative time by limiting recipient vessels dissection procedure as well as the need for shorter flap pedicle (Hamdi et al, 2004;Vollbach et al, 2016). However, this option is limited by the technical difficulty and the potential lack of suitable perforators (Follmar et al, 2011;Hamdi et al, 2004;Vollbach et al, 2016).…”
Section: Lorenzetti Et Al Investigated the Effects Of These Parametementioning
confidence: 99%
“…IMA perforators, when preserved, are readily available, obviating the need for further surgical dissection and morbidity. Likewise, their more superficial entrenchment means less interference from cardiorespiratory chest‐wall motion and affords the use of shorter flap pedicles (Baek & Yoon, ; Follmar et al, ; Hamdi et al, ; Saint‐Cyr, Chang, et al, ; Vollbach et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The next evolution, the rib sparing approach to the internal mammary vessels, may not be possible in limited interspaces, still necessitating removal of cartilage (Sacks & Chang, ). With the development of microsurgical techniques, several authors have reported the successful use of perforating branches of the internal mammary artery (IMA) (Follmar et al, ; Hamdi, Blondeel, Van Landuyt, & Monstrey, ; Munhoz et al, ; Saint‐Cyr, Chang, Robb, & Chevray, ; Vollbach, Heitmann, & Fansa, ). Perforator to perforator surgery limits the amount of dissection necessary, and obviates the need for rib removal and sacrifice of the IMA for future revascularization procedures (Follmar et al, ; Koshima, Yamamoto, Narushima, Mihara, & Iida, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation